The Courage to Care—An innovative arts-based event to engage students and the local community to reflect on Australian nurses' roles in the First World War and after. (December 2016) - McAllister, Margaret; Davis, Susan; Brien, Donna Lee; Rogers, Irene; Flanagan, Wendy; Howie, Virginia; Dargusch, Jo
Summary: There is a large body of work that documents the history of the nursing profession and the experiences of nurses during significant historical eras such as the First World War. Yet learning about nursing history is commonly a tiny, or absent, component in the undergraduate nursing curriculum. This paper discusses an innovative project that had multiple aims. A primary aim was to engage nursing students and educators in a project that valued nursing history by integrating it into an event to celebrate International Nurses Day. As the paper will explain, other aims were in organising the event so that it capitalised on particular creative arts strengths within the faculty, offering cross-disciplinary connections, engagement and appreciation. A Readers' Theatre event, involving academics and students in nursing, creative arts and education, was conceived, developed and performed for the community. The theme was the experiences of First World War nurses and how they encapsulated values important to nursing today – the 6 Cs – which guide high standards of nursing. The 6 Cs are care, compassion, competence, communication, courage and commitment. We called the Readers' Theatre "The Courage to Care", and this involved a 4 month process of script development, event planning and a performance. This process and outcomes were evaluated, prompting a reflection on the strengths and challenges of working in this creative way to engage a wide group of stakeholders to advance the profession of nursing. Highlights: History of nursing occupies a tiny component in many nursing programs. A multi-disciplinary project was devised to celebrate International Nurses Day, incorporate the 6Cs that summarise core nursing values, and capitalise on the creative arts. Results of the study found that new knowledge about nursing history was developed, a deepening of professional self-understanding was gained, and a greater appreciation for creative practice and multi-disciplinary collaboration was achieved.